A decision model on the repair and maintenance of shipping containers - Niclas Hoffmann; Robert Stahlbock; Stefan Voß (Journal of Shipping and Trade (JST), 2020)
The use of shipping containers for the transport of goods has become indispensable and a crucial factor for globalization by providing inexpensive and safe transport opportunities. It is expected that the number of globally operating containers will increase in the near future. Despite a high technical modernisation of the logistic chain, the container still faces a risk of damage at any time and any place within the transport chain. In principle, a container is taken out of service, when a damage is recognized. Different causes of damage exist and various types of damage could occur to the container, ranging from minor to substantial major ones that do not permit the continued proper use of the container. Thus, an individual decision on repair and maintenance (R&M) for each damaged container is necessary. Aside from technical aspects, it has to be decided from an economical perspective whether a repair should be performed. A profound decision should consider various criteria like, e.g., repair costs, lifespan of the container, future yields and possible sales price. Based on a regulatory, practical, and scientific view, this paper proposes a multi-criteria decision model for the economic decision on the R&M of a damaged container. Implemented in Microsoft Excel, this decision model is easily applicable. The user can deduce a first (limited) guidance for dealing with a respective damaged container based on its current state and general market conditions.
Keywords: 650; Container logistics; Decision support; Repair and maintenance